The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1096/fj.14-255398
|View full text |Cite
|
Sign up to set email alerts
|

Melanocyte pigmentation inversely correlates with MCP‐1 production and angiogenesis‐inducing potential

Abstract: The incidence of certain angiogenesis-dependent diseases is higher in Caucasians than in African Americans. Angiogenesis is amplified in wound healing and cornea models in albino C57 mice compared with black C57 mice. Moreover, mouse and human melanocytes with low pigmentation stimulate endothelial cell (EC) proliferation and migration in vitro more than melanocytes with high pigmentation. This effect is due, in part, to the secretion of an angiogenic protein called fibromodulin (FMOD) from lowly pigmented mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…Finally, recent reports have shown that fibromodulin promotes in vitro and in vivo angiogenesis [ 492 ], and this is particularly prominent in melanocyte-secreted fibromodulin [ 493 ]. Mechanistically, fibromodulin appears to be secreted at high levels in low pigmented melanocytes and it stimulates the secretion of monocyte chemotactic protein-1, which is a powerful angiogenic factor [ 494 ].…”
Section: Small Leucine-rich Proteoglycans/slrpsmentioning
confidence: 99%
“…Finally, recent reports have shown that fibromodulin promotes in vitro and in vivo angiogenesis [ 492 ], and this is particularly prominent in melanocyte-secreted fibromodulin [ 493 ]. Mechanistically, fibromodulin appears to be secreted at high levels in low pigmented melanocytes and it stimulates the secretion of monocyte chemotactic protein-1, which is a powerful angiogenic factor [ 494 ].…”
Section: Small Leucine-rich Proteoglycans/slrpsmentioning
confidence: 99%
“…CXCL5 is also part of the CXC chemokine family and controls angiogenic properties by enhancing microvascular endothelial cell migration and tube formation [32]. Monocyte chemotactic protein-1 (MCP-1) (also called chemokine (C-C motif) ligand 2, CCL2) upregulates FGF, PDGF, and VEGF expression, stimulates EC proliferation and migration, and induces MMP-1 secretion by ECs to degrade the ECM [65]. In addition to these ve proangiogenic factors, the expression of three traditional proangiogenic factors in placental tissue was also increased.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it stimulates proliferation and migration of endothelial cells and may contribute to the mechanism of increased pathological angiogenesis in lighter skin. Adini et al demonstrated that CCL2 was highly upregulated in nonpigmented mouse melanocytes compared to the pigmented cells. It was also shown that Caucasians have 2‐fold higher serum levels of CCL2 protein than African Americans.…”
Section: Discussionmentioning
confidence: 99%